2005
DOI: 10.1124/jpet.105.083337
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity of Melanocortin 4 Receptor Peptide and Nonpeptide Agonists: Evidence for Ligand-Specific Conformational States

Abstract: Agonists of the melanocortin 4 (MC4) receptor have potential pharmaceutical benefit in the treatment of obesity and sexual dysfunction. In this study, we have compared the ability of a number of peptide and nonpeptide agonists to activate a FLAG-tagged human MC4 (FMC4) receptor, as measured by both cAMP accumulation and calcium mobilization using a fluorometric imaging plate reader (FLIPR). In addition, we have analyzed the ability of these agonists to cause receptor internalization, as measured by fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
2
25
0
3
Order By: Relevance
“…Biased signaling, as an important concept in GPCR intracellular signaling, has been identified in many members of GPCR family [97, 98]. Data from us and others [45, 47, 51, 52, 56] suggested that neural MCRs are able to selectively stabilize particular receptor active conformations and preferentially trigger distinct signaling pathways, consistent with the multi-state model of receptor activation and biased signaling in other GPCRs.…”
Section: Biased Signaling At Neural Mcrssupporting
confidence: 70%
See 1 more Smart Citation
“…Biased signaling, as an important concept in GPCR intracellular signaling, has been identified in many members of GPCR family [97, 98]. Data from us and others [45, 47, 51, 52, 56] suggested that neural MCRs are able to selectively stabilize particular receptor active conformations and preferentially trigger distinct signaling pathways, consistent with the multi-state model of receptor activation and biased signaling in other GPCRs.…”
Section: Biased Signaling At Neural Mcrssupporting
confidence: 70%
“…However, increasing number of recent studies have demonstrated that similar to other GPCRs, neural MCRs can couple to other G proteins or signaling mediators to trigger the downstream signaling pathways, in addition to the conventional Gαs-cAMP signaling pathway. Biased signaling was also proposed for neural MCRs since we and others identified some biased mutant neural MCRs which selectively trigger signaling pathways upon ligand stimulation, and some biased agonists which can selectively induce signaling pathways through neural MCRs [45-56]. …”
Section: Introductionmentioning
confidence: 99%
“…Functional selectivity has been well described among amine receptors including serotonergic (Roth and Chuang, 1987;Berg et al, 1998), dopaminergic (Lewis et al, 1998;Gay et al, 2004), and adrenergic (Jim et al, 1985) receptors. Ligand functional selectivity has also been demonstrated for several other peptide receptors (Hunyady et al, 1994;Whistler et al, 1999;Zhang et al, 1999;Kapusta et al, 2005;McLaughlin et al, 2005;Nickolls et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…functionally selective agonists. Biased agonism, has been identified for many therapeutically important GPCRs such as α 1 -and β-adrenergic receptors [16,[23][24][25], μ-opioid receptors (MOR) [26,27], cannabinoid receptors [28,29], D 2L and D 1 dopamine receptors [30][31][32][33], serotonin receptors [17,34,35], chemokine receptor CCR7 [36,37], gonadotropin-releasing hormone receptors [38,39], parathyroid hormone 1 receptors (PTH1R) [40,41], angiotensin 1A (AT 1A ) receptors [42] or MC4 melanocortin receptors [43].…”
Section: Przykłady Selektywności Funkcjonalnejmentioning
confidence: 99%